2014
DOI: 10.1155/2014/379847
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Capping Protein CapG Is a Putative Oncogene Involved in Migration and Invasiveness in Ovarian Carcinoma

Abstract: The actin binding protein CapG modulates cell motility by interacting with the cytoskeleton. CapG is associated with tumor progression in different nongynecologic tumor entities and overexpression in breast cancer cell lines correlates with a more invasive phenotype in vitro. Here, we report a significant CapG overexpression in 18/47 (38%) of ovarian carcinomas (OC) analyzed by qRealTime-PCR analyses. Functional analyses in OC cell lines through siRNA mediated CapG knockdown and CapG overexpression showed CapG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…75 Remarkably, this paper was the first to identify MCP as cancer biomarker. Other studies on different human malignancies [76][77][78][79][80] validated MCP as a cancer biomarker, further supporting the use of dogs as useful models for human cancer. Studies on the serum proteome changes of canine lymphoma have been carried out by combining ion exchange chromatography and surface-enhanced laser desorption ionisation (SELDI) mass spectrometry.…”
Section: View Article Onlinementioning
confidence: 73%
“…75 Remarkably, this paper was the first to identify MCP as cancer biomarker. Other studies on different human malignancies [76][77][78][79][80] validated MCP as a cancer biomarker, further supporting the use of dogs as useful models for human cancer. Studies on the serum proteome changes of canine lymphoma have been carried out by combining ion exchange chromatography and surface-enhanced laser desorption ionisation (SELDI) mass spectrometry.…”
Section: View Article Onlinementioning
confidence: 73%
“…As mentioned above, the causal role for CAPG in tumorigenesis has been extensively explored. In addition, recent study with a small sample size demonstrated a positive association of a CAPG variant with a rare fallopian tube tumor [21]. Along with the above evidence, we hypothesized that CAPG might be crucial for the development and progression of malignancy.…”
Section: Introductionmentioning
confidence: 72%
“…Recent evidence that CAPG p.R335H was associated with risk of fallopian tube carcinoma in a small case-control study promoted us to examine the effect of the SNV of CAPG on various cancers using large-sized autopsy cases [21]. Most previous reports demonstrated a positive association between cancer and CAPG protein expression [5][6][7][8][9][10][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that CapG is associated with invasion and metastasis in various types of malignancy (15)(16)(17). However, to the best of our knowledge, the effect of CapG in primary CRC was not investigated prior to the present study.…”
Section: Discussionmentioning
confidence: 92%